2020
DOI: 10.1111/cbdd.13706
|View full text |Cite
|
Sign up to set email alerts
|

Multimeric TAT peptides are effective in vitro inhibitors of Staphylococcus saprophyticus

Abstract: TAT (48-60) is a tridecapeptide from the envelope protein of HIV that was previously shown to possess cell-penetrating properties and antibacterial activity, making it a potential drug delivery agent for anticancer drugs and as antibacterial compound. Previous reports indicated that dimerization enhances the desired bioactivity of TAT; hence, we sought to synthesize multimeric TAT peptides. Herein, we describe the effects of multimerization on the antibacterial activity and secondary structure of the peptide. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Interestingly, the TAT derived from human immunodeficiency virus (HIV) has been widely employed in the construction of cellular internalization materials, including lipid nanoparticles that penetrate the blood–brain barrier and click chemistry to link camptothecin, for fighting cancer . In addition, TAT, with its high surface positive charges, can localize bacterial membranes on a large scale and provide noncovalent forces to capture bacteria, thus forming amphiphilic materials distinct from antibiotics for sterilization. , Therefore, pathogenic microorganism affinity motifs based on the highly positively charged TATs are regarded as biomaterials with superior properties. Our group previously demonstrated that Tryptophan (Trp)-zipper-based antimicrobial motifs could form self-assembled micelles through cationic−π bonds and aromatic stacking with aromatic rings and, by virtue of this, possess robust antimicrobial capabilities .…”
mentioning
confidence: 99%
“…Interestingly, the TAT derived from human immunodeficiency virus (HIV) has been widely employed in the construction of cellular internalization materials, including lipid nanoparticles that penetrate the blood–brain barrier and click chemistry to link camptothecin, for fighting cancer . In addition, TAT, with its high surface positive charges, can localize bacterial membranes on a large scale and provide noncovalent forces to capture bacteria, thus forming amphiphilic materials distinct from antibiotics for sterilization. , Therefore, pathogenic microorganism affinity motifs based on the highly positively charged TATs are regarded as biomaterials with superior properties. Our group previously demonstrated that Tryptophan (Trp)-zipper-based antimicrobial motifs could form self-assembled micelles through cationic−π bonds and aromatic stacking with aromatic rings and, by virtue of this, possess robust antimicrobial capabilities .…”
mentioning
confidence: 99%